2009
DOI: 10.1111/j.1476-5381.2009.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide attenuates nitric oxide‐driven angiogenesis by interacting with soluble guanylyl cyclase

Abstract: Background and purpose: Nitric oxide (NO) promotes angiogenesis by activating endothelial cells. Thalidomide arrests angiogenesis by interacting with the NO pathway, but its putative targets are not known. Here, we have attempted to identify these targets. Experimental approach: Cell-based angiogenesis assays (wound healing of monolayers and tube formation in ECV304, EAhy926 and bovine arterial endothelial cells), along with ex vivo and in vivo angiogenesis assays, were used to explore interactions between tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…Finally, the fluorescence images of the stained cells were captured by using an Olympus fluorescence microscope. 25,26 …”
Section: Methodsmentioning
confidence: 99%
“…Finally, the fluorescence images of the stained cells were captured by using an Olympus fluorescence microscope. 25,26 …”
Section: Methodsmentioning
confidence: 99%
“…These molecules are also thought to act by oxidation and desensitisation of the heam group to NO. A growing body of evidence has implicated sGC as a player in the angiogenesis pathway [7], [25], [27], [28], [29], [30], a popular pathway to drug in the inhibition of tumor vascularisation [31], [32] and to combat diabetic retinopathy [33], [34]. An as-yet unexploited avenue for pharmaceutical development would be targeting the catalytic domain for activation or inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…It owes this potent anti-angiogenic activity to direct inhibition of endothelial cell proliferation, decreasing the plasma levels of basic fibroblast growth factor and downregulating the expression of neuropilin-1, a vascular endothelial growth factor receptor that is overexpressed in AML and shows a significant correlation with lower survival [7,8]. Majumder et al [9] showed that thalidomide attenuated nitric oxide-driven angiogenesis by interacting with soluble guanylyl cyclase. In addition to anti-angiogenic activity, thalidomide probably also has anti-leukemic effects through other mechanisms, such…”
Section: Introductionmentioning
confidence: 99%